Pengaruh Fintech Payment, Kontrol Diri Dan Literasi Keuangan Syariah Terhadap Manajemen Keuangan Pribadi Pada Komunitas Genbi Bengkulu - Laila Tri Oktavia; Idwal B; Miko Polindi (JPSDa: Jurnal Perbankan Syariah Darussalam, 2025)
This study aims to analyze the influence of Fintech Payment, self-control, and Islamic financial literacy on personal financial management within the Generasi Baru Indonesia (GenBI) community in Bengkulu. The research employs a quantitative approach, with data collected through questionnaires distributed to 175 respondents. The data were analyzed using multiple linear regression with the assistance of SPSS version 25. The analysis results show that, partially, Fintech Payment has a positive and significant effect on personal financial management with a significance level of 0.042. The self-control variable also has a significant influence, with a significance value of 0.003, while Islamic financial literacy demonstrates the most significant impact, with a value of 0.000. Simultaneously, the three variables have a positive and significant effect on personal financial management, as evidenced by a significance value of 0.000 (< 0.05). Therefore, these variables contribute significantly to improving the personal financial management skills of GenBI Bengkulu members.